A quaternary TiO2/ZnO/RGO/Ag nanocomposite with enhanced visible light photocatalytic performance. (16th June 2017) - K. S., Divya; Xavier, Marilyn Mary; P. V., Vandana; V. N., Reethu; Mathew, Suresh
Abstract : Synthesis and photocatalytic application of a quaternary TiO2 /ZnO/RGO/Ag nanocomposite under visible light. Abstract : "Together we can make the difference". A quaternary TiO2 /ZnO/RGO/Ag nanocomposite exhibits enhanced photoactivity compared to TiO2 /ZnO/RGO and TiO2 /ZnO for the degradation of rhodamine B under visible light. The quaternary composite was synthesized via facile microwave irradiation of dispersed TiO2 /ZnO and RGO/Ag nanocomposites. X-ray diffraction analysis and high-resolution transmission electron microscopy revealed the presence of TiO2, ZnO, RGO and Ag in the composite. Photoelectrochemical measurements and time correlated single photon counting (TCSPC) analysis confirmed that the presence of RGO sheets and Ag enhanced the photocatalytic properties of the nanocomposite. The enhanced charge separation and the low recombination rate of photogenerated charge carriers in the composite with the assistance of excellent co-catalysts, RGO and Ag, have also been investigated.